PENGEMBANGAN FORMULA SNACK BAR SORHILA DENGAN KOMBINASI TEPUNG SORGUM, KACANG HIJAU DAN LABU KUNING BAGI ANAK AUTIS: PENGEMBANGAN FORMULA SNACK BAR SORHILA - Juni Gressilda Louisa Sine; Santa Luciana Diaz Vera da Costa (Poltekkes Kemenkes Kupang, 2022)
Autism is a severe neurobiological developmental disorder that occurs in children aged less than 3 years and will continue if no intervention is carried out. Hyperactive behavior in children with autism can be overcome by choosing the type of food ingredients. Gluten and casein are two types of proteins that affect people with autism. Gluten is a protein found in the wheat group, while casein is a protein found in milk and its products. The purpose of this study was to develop an alternative snack product for autistic children in the form of a Sorhila Snack bar a combination of sorghum flour, green beans and pumpkin that were free of gluten and casein. This research was conducted using an experimental method, using a Completely Randomized Design (CRD) with 3 treatments, namely: P1 = Combination of 80 grams of sorghum flour: 30 grams of mung bean flour: 20 grams of pumpkin flour, P2 = Combination of 70 grams of sorghum flour: peanut flour 40 grams of green: 20 grams of pumpkin flour, P3 = Combination of 60 grams of sorghum flour: 50 grams of green bean flour: 20 grams of pumpkin flour. Each treatment consisted of 3 replications so that the study consisted of 9 experimental units. The acceptability of the Sorhila snack bar was carried out by organoleptic tests (including color, aroma, texture and taste) using 30 panelists, while the nutritional content was carried out using the proximate test. Organoleptic test data were analyzed using the Kruskal Wallis statistical test because the data were not normally distributed and continued with the Mann Whitney test to determine the significant difference between the treatment groups